Effects of Coronavirus-19 Induced Loneliness on Mental Health: Sleep Quality and Intolerance for Uncertainty as Mediators - Gu, Simeng; He, Zhengming; Sun, Lianwang; Jiang, Yao; Xu, Minghong; Feng, Guangkui; Ma, Xianjun; Wang, Fushun; Huang, Jason H. (Frontiers in Psychiatry, 2021)
Objective: The aim of the study is to investigate effects of loneliness on individual’s mental health and the mediating effects of intolerance of uncertainty and sleep quality in the post Coronavirus-19 period, especially for the young people. Methods: The questionnaires used in this study include UCLA loneliness scale (UCLA-3), the Pittsburgh Sleep Quality Index (PSQI), intolerance for uncertainty (IU) and the Chinese version of DASS-21. A total number of 289 subjects were recruited in the study, which includes 209 females (72.3%), 80 males (27.7%); and 212 students (73.4%), 77 working staffs (26.6%). Results: The results showed that: (1) people have high levels of loneliness, anxiety, depression and stress, and poor sleep quality; (2) the mediating effect of intolerance for uncertainty in the relationship of loneliness and mental health is significant (effect size = 0.178, 95% CI confidence interval: [0.115，0.241]), and the mediating effects of sleep quality in the relationship between loneliness and mental health is significant (effect size = 0.127, 95% CI confidence interval: [0.017, 0.239]). Conclusion: Loneliness invokes a stronger self-concerned inadaptability to threat response and may lead to more mental diseases through more serious intolerance for uncertainty and insomnia.